THE MECHANISM OF ANGULAR MOMENTUM TRANSFER IN ACCRETION STELLAR DISKS BY LARGE VORTICAL STRUCTURES - Lugovskiy, A.; Chechetkin, V.; Sychugov, K. (Одеські астрономічні публікації, 2012)
Large-scale vortical flows arising in shear flows of stellar accretion disks with Keplerian azimuthal velocity distributions is investigated. The two reasons of the development of large-scale instability is shown: hydrodynamical instability and magnetorotational instability (MRI). The presence of large-scale structures leads to angularmomentum redistribution in the disk.